Impact of codoping on structure, optical and scintillation properties of Gd₂Si₂O₇-based crystals - Gerasymov, Ya.V.; Baumer, V.N.; Neicheva, S.V.; Starzhinskiy, N.; Tarasov, V.A.; Zelenskaya, O.V.; Sidletskiy, O.Ts. (Functional Materials, 2013)
Impact of codoping on structure, optical, and scintillation properties of Gd₂Si₂O₇:Ce (GPS:Ce) crystals doped with La³⁺ and Sc³⁺ have been considered. GPS:Sc,Ce and GPS:La,Ce crystals have been obtained by the Top Seeded Solution Growth method with SiO₂ self-flux. Codoping influences the type of structure, density, as well as decreases self-absorption of luminescence in crystals. Temperature dependence of light yield at elevated temperatures have been obtained and compared to other pyrosilicate based crystals.